What Colour is Theoreticism? Faust Reading Althusser - Romé, Natalia (2015)
Far from disregarding it, Althusserian “theoreticism” is a long detour through the problem of thinking politics. This Chapter focuses on some traces laying on the surface of Lire le Capital, through the references to a few phrases of Goethe´s Faust and its echoes within a Marxist heritage. Signs that indicate on the surface of the writing, the mode in which Althusserian though exceeds the epistemological ground to enhance, through the tension between Theory and Practice, a problematic regarding time, that opens spaces for political thought.